2018
DOI: 10.4314/ijbcs.v12i3.1
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of betacyanoalanine synthase from <i>Pseudomonas straminea</i>

Abstract: Beta-cyanoalanine synthase (EC 4.4.1.9) is a cyanide detoxifying enzyme obtained from Pseudomonas straminea isolated from the effluents of Iron and Steel Smelting Company in Ile-Ife, Osun State. The effluent water samples were screened for their ability to detoxify cyanide and isolates obtained were then screened for b-cyanoalanine synthase production. The samples were screened for their ability to detoxify cyanide and isolates obtained were then screened for β-Cyanoalanine Synthase production. The enzyme was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…The decline in rhodanese production may be due to exhaustion of the nutrients or accumulation of other products or metabolites which are both inhibitory to the growth of the bacterium and rhodanese production. This result agrees with the findings of Okonji et al (2018) who observed a decrease in metabolite production after 15 hours of incubation. Linawati et al (2002) also reported the influence of environmental conditions on the production of pigment by Serratia marcescens.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The decline in rhodanese production may be due to exhaustion of the nutrients or accumulation of other products or metabolites which are both inhibitory to the growth of the bacterium and rhodanese production. This result agrees with the findings of Okonji et al (2018) who observed a decrease in metabolite production after 15 hours of incubation. Linawati et al (2002) also reported the influence of environmental conditions on the production of pigment by Serratia marcescens.…”
Section: Discussionsupporting
confidence: 93%
“…The ability of P. putida and B. pumilus to make use of cyanide as carbon source was also reported by Kandasamy et al (2015). Okonji et al (2018) also reported the ability of Pseudomonas straminea to make use of peptone as nitrogen source. The high cyanide tolerance of K. oxytoca observed was probably due to its ability to synthesize rhodanese as a means of surviving in cyanide contaminated environment.…”
Section: Discussionmentioning
confidence: 56%
“…a pyridoxal phosphate-dependent enzyme (Arenas-Alfonseca et al, 2018) that catalyzes the substitution of L-cysteine sulfhydryl moiety with cyanide, forming the non-protein amino acid, βcyanoalanine with the release of hydrogen sulfide (Figure 1A) (Okonji et al, 2018). Released H2S can block the mitochondrial respiratory pathway and can be further detoxified by O-acetyl-Lserine sulfhydrylase (OASS) (Alvarez et al, 2012).…”
mentioning
confidence: 99%
“…The host plant range of TSSM includes a number of plants that synthesize cyanogenic glucosides. These compounds are not toxic on their own and require hydrolysis to generate a reactive hydroxynitrile that releases toxic HCN (Okonji et al, 2018). The hydrolysis occurs upon tissue disruption that can occur during herbivore feeding.…”
mentioning
confidence: 99%